Next-Generation Sequencing: Bioinputs for Agriculture Innovation - Sauka, Diego Herman (2024)
Bioinputs, a sustainable and potent alternative to chemical products used in agriculture, find a position of radical change with the advent of next-generation sequencing (NGS) techniques. These bioinputs, derived from microorganisms, assure the reduction of environmental impact and are able to increase food production. However, proper bioinput development will require the identification of these microorganisms at a level of detail, thereby ensuring a standardized approach. The assessment of potential risks to these microorganisms is thus critical for the safety and efficacy in use, while global collaboration can enable the establishment of standards to be adopted universally.